Value-Based Management Accounting for Improving Financial and Non-Financial Performance - Yosphia Fahruddiana (PT. BATARI EDU CALYA, 2025)
This study investigates the implementation and impact of value-based management accounting (VBMA) practices on both financial and non-financial performance within Indonesian business contexts. The research synthesizes empirical evidence from various Indonesian industries to examine how management accounting practices contribute to organizational value creation and performance enhancement. Employing a quantitative research methodology with structural equation modeling (SEM) analysis, this study analyzes the relationships between management accounting system usage, value chain integration, and multidimensional performance outcomes. The findings reveal that advanced management accounting practices significantly influence both financial metrics (profitability, liquidity, and market value) and non-financial indicators (customer satisfaction, service quality, and operational efficiency). Furthermore, the study demonstrates that value-based approaches to management accounting facilitate superior decision-making processes and enhance organizational competitiveness in the Indonesian market. The research contributes to the theoretical understanding of management accounting evolution while providing practical implications for Indonesian enterprises seeking to optimize their performance measurement and management systems.